2019
DOI: 10.1089/jpm.2018.0509
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Effectiveness of a Mnemonic Approach to Teach Residents How to Assess Goals of Care

Abstract: Background: Shared decision making is a collaborative process that allows patients, or their surrogates, and clinicians to make health care decisions together. There is an imperative to teach young physicians early in their training the importance of engaging in a shared decision-making process to define overall goals of care (GOC). The PERSON mnemonic proposes a structured format that allows providers to evaluate GOC across the spectrum of serious illnesses, outside of breaking bad news or end-of-life plannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…This study concluded that although not all letters of the mnemonic were remembered 7 months later, most of the participants were still able to apply it. 6 A 2018 study likewise demonstrated a decrease in peripheral intravenous infiltration with the application of a 5-letter mnemonic by pediatric registered nurses. 7 Here we provide clinicians with an alphabetical mnemonic to guide their pharmacotherapeutic decisions when treating patients with HFrEF.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…This study concluded that although not all letters of the mnemonic were remembered 7 months later, most of the participants were still able to apply it. 6 A 2018 study likewise demonstrated a decrease in peripheral intravenous infiltration with the application of a 5-letter mnemonic by pediatric registered nurses. 7 Here we provide clinicians with an alphabetical mnemonic to guide their pharmacotherapeutic decisions when treating patients with HFrEF.…”
Section: Introductionmentioning
confidence: 91%
“…Success was evaluated by a presurvey and postsurvey completed 7 months after the session. 6 Results demonstrated that 29 of 30 participants reported the mnemonic made sense immediately after the session, and 28 of 30 felt it made sense 7 months later. Approximately 93% reported that the mnemonic was beneficial and useful immediately after the session, and 86.67% reported it was useful 7 months later.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“… 1 , 2 , 3 , 4 , 5 To redress this predicament, medical communication experts have published a variety of communication models designed to aid and promote SIC facilitation. 6 , 7 , 8 , 9 , 10 We three clinician-educators are among their many beneficiaries. Yet despite their value, our experience in communication education and clinical encounters has revealed three recurring impediments to their instruction, retention, and usefulness.…”
Section: Introductionmentioning
confidence: 99%